Role of Ultrasonography in the Evaluation of Thyroid Nodule with Fine Needle Aspiration Cytology ( FNAC) Correlation - Shrestha, Elina; Thapa, Narayan Bikram; Rajbhandari, Shankar Bahadur Singh (Nepal Journal of Medical Sciences, 2021)
Introduction: Thyroid nodules are commonly encountered pathologies worldwide. High-resolution ultrasonography is the first-line investigation for the evaluation of thyroid nodules as it is a cheap, quick, non-invasive, easily accessible modality without radiation hazards. Our major concern is to select suspicious thyroid nodules and early detection of malignancy. Fine needle aspiration cytology (FNAC) when correlated with ultrasonographic imaging features helps inaccurate assessment of categorizing thyroid nodules. USG guided FNAC is a widely practiced procedure because it is a less time-consuming simple procedure and helps to locate suspicious sites more precisely to get a higher yield. Methods: Total 70 patients with thyroid nodules detected by ultrasonography dated from October 2020 till September 2021 were enrolled in the study. The enrolled patients had FNAC in the same settings. The ultrasonographic characteristics of thyroid nodules were assessed and correlated with cytology reports. Results: Amongst 70 patients, 84.3% were female and 15.7% were male with a male:female ratio of 1:1.8. The mean age was 48.6 ± 13.2 years. Out of 70 patients, 49 patients had benign nodules while 21 patients had malignant nodules. Nodules that have characteristics like ill-defined border, hypoechoic echotexture, having predominantly solid components, microcalcification, increased central vascularity, and absence of halo are good indicators of malignancy. The sensitivity, specificity, positive, negative predictive value, and accuracy of ultrasonography were 72%, 91.8%,78.9%, 88.2%, and 85.7 % respectively. Conclusion: Ultrasonography is the most accurate, sensitive, and specific modality in categorizing thyroid nodules. A significant correlation of p< 0.05 was observed between ultrasonography with FNAC resulting in good accuracy. There is less chance of missing malignancy which helps to reduce unnecessary surgeries and promotes surgical intervention.